The assessment of commitment: Advantages of a unidimensional, target-free approach. - Klein, Howard J.; Cooper, Joseph T.; Molloy, Janice C.; Swanson, Jacqueline A. (Journal of Applied Psychology, 2014)
This study presents a new approach to assessing commitment reflecting the Klein, Molloy, and Brinsfield (2012) reconceptualization. Klein et al. recast the construct to address issues hindering commitment scholarship, but their claims cannot be tested with existing measures. This paper presents a 4-item measure consistent with the Klein et al. conceptual definition, a measure intended to be unidimensional and applicable across all workplace targets. Our purpose is to present the development of and provide initial validity evidence for this new commitment measure and to compare it to existing alternative measures. Hypotheses around these objectives were tested with data gathered across 5 samples yielding 2,487 participants representing a wide range of jobs, organizations, and industries. Each sample examined a unique set of variables and targets that together provide a comprehensive test of this new measure relative to 8 different targets, several constructs within the nomological network, and 4 prior commitment measures. Results support our hypotheses regarding (a) the measure's properties and structure, (b) convergence and divergence with prior measures of commitment and other constructs in the nomological network, and (c) advantages over prior measures. These findings support the validity of this new approach to assessing commitment, laying the foundation for future research to address critiques of the commitment construct; better examine the multiple commitments individuals simultaneously hold; and bring consistency, synergy, and integration to commitment scholarship across workplace targets. The conceptual, methodological, and practical benefits of the measure are discussed, along with study limitations and future research opportunities.